Investigating glyphosate tolerance mechanisms in the liverwort Marchantia polymorpha - Caygill, SG (2023)
The evolution of herbicide resistance in weeds is a threat to global crop yields. The aim of this thesis is to increase our understanding of the evolution and mechanisms of herbicide resistance. To achieve this, I first determine the phylogenetic relationships of both the ATP-binding cassette (ABC) transporter and uridine diphosphate glycosyltransferase (UGT) protein superfamilies within the Archaeplastida lineage. Proteins from these families confer non-target site resistance (NTSR) in populations of weeds. I also determine that the liverwort Marchantia polymorpha is naturally tolerant to the non-selective herbicide glyphosate. Using enzyme activity assays, I demonstrate that glyphosate tolerance in M. polymorpha is not due to a resistant version of the glyphosate target EPSPS. Instead, I discover a novel form of glyphosate tolerance conferred by the peptidoglycan biosynthesis enzyme MurA, which is structurally similar to EPSPS. By expressing MurA in the angiosperm Arabidopsis thaliana and generating murA loss-of-function mutants in M. polymorpha, I determine that MurA confers glyphosate tolerance independently from its function in peptidoglycan biosynthesis. I show that MpMurA catalyses the same reaction as EPSPS, transferring the enolpyruvyl moiety of phosphoenolpyruvate (PEP) to shikimate-3-phosphate (S3P) forming 5-enolpyruvylshikimate-3-phosphate (EPSP) product. However, like EPSPS, it is also inhibited by glyphosate. I therefore propose that MurA confers glyphosate tolerance either through a mechanism analogous to target-site overexpression or by binding glyphosate, making it less available to inhibit EPSPS. Through a metabolomic analysis, I also show that the metabolic response to glyphosate treatment in M. polymorpha differs from that in A. thaliana. This may be a result of, or contribute to, glyphosate tolerance in M. polymorpha. These results therefore demonstrate a novel form of glyphosate tolerance and determine the physiological impacts of glyphosate treatment that may contribute to its mode of action.